1999
DOI: 10.1023/a:1026679123148
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: To date, tests of small intestinal passive permeability have involved the ingestion of test molecules whose permeation is assessed indirectly by measuring their urinary recovery. Excretion ratios of marker molecules (eg, lactulose-to-mannitol excretion ratio, LMER) are useful clinically. Measurement of permeability markers in serum would improve the convenience of the tests. Our aim was to assess small intestinal permeability in celiac patients using serum lactulose and mannitol levels with calculation of lact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…The observed pattern of mannitol absorption in the CW28 piglets corresponded to previously reported values [19]. Although some mannitol passes through the epithelial layer via the paracellular route, it is mostly absorbed via the transcellular route via water-filled pores in the enterocyte membrane, making mannitol a surrogate marker of functional mucosal mass in the SI [18]. In the pre-weaning period, the trend for the IS groups (when combined) to have lower mannitol concentrations than the CW28 group suggests that IS reduces intestinal surface area before weaning.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The observed pattern of mannitol absorption in the CW28 piglets corresponded to previously reported values [19]. Although some mannitol passes through the epithelial layer via the paracellular route, it is mostly absorbed via the transcellular route via water-filled pores in the enterocyte membrane, making mannitol a surrogate marker of functional mucosal mass in the SI [18]. In the pre-weaning period, the trend for the IS groups (when combined) to have lower mannitol concentrations than the CW28 group suggests that IS reduces intestinal surface area before weaning.…”
Section: Discussionsupporting
confidence: 84%
“…A subsample of piglets from sows in three of the batches (a total of nine piglets per treatment) were subjected to sugar absorption tests (SAT) as markers of intestinal absorption based on methodologies described by Thymann et al [17], Cox et al [18] and Berkeveld et al [19]. Briefly, two piglets were selected per litter and sugar absorption across the GIT using either 10% mannitol (≄98%; Sigma Aldrich, St Louis, MO, USA) (5 mL/kg body weight (BW)) or 10% galactose (≄99%; Sigma Aldrich, St Louis, MO, USA) (5 mL/kg BW) was assessed.…”
Section: Methodsmentioning
confidence: 99%
“…IP is usually expressed as a percentage of the excreted amount in urine to the administered amount of a certain test drug, and the normal value is <2% 19. In clinical practice, clinicians most commonly use polysaccharides, such as lactulose, which are relatively large molecules and pass through the intercellular space of the intestinal mucosa and monosaccharides, such as lamnose or mannitol, which are relatively small molecules and move into the cell interior 20. We used this test in the study.…”
Section: Discussionmentioning
confidence: 99%
“…1a). A defect in the paracellular pathway is relevant not only to this animal model but also to celiac disease [16, 17]. We have previously shown that in HCD4/HLA-DQ8 mice, gliadin causes an increased flux of the transcellular macromolecular probe HRP as well as an augmented short circuit current, which is not observed at this magnitude in haplotype controls (HLA-DQ6) and wild-type (C57BL/6) mice treated with gliadin [12, 14].…”
Section: Discussionmentioning
confidence: 99%